Multiplying sites of sovereignty through Community and Constituent Services at the National Museum of the American Indian? - Kylie Message (Museum & Society, 2009)
My twofold aim in this article is (i) to initiate discussion about issues of governance and sovereignty in order to strengthen lateral connections between the disciplines of museum studies and citizenship studies, and (ii) to examine the National Museum of the American Indian’s capacity to challenge concepts of citizenship that reflect traditional national identity discourses. The article has three parts. The first introduces the National Museum of the American Indian and outlines its aspiration to become an ‘intermediary institution’. Second, I present a theoretical engagement with issues of cultural and political sovereignty and citizenship. Contextualized by this theoretical framework, the third section provides a brief case-study that questions if the incorporation of the 2007 National Powwow into the programme of annual events organized by Community and Constituent Services and Public Programs might be perceived as helping the Museum achieve its strategic goals and responsibilities to Native and non-Native visitors, and to its Native constituents. If so, can the powwow (or other outreach activities) also offer an alternative to the traditional ways in which people have understood and experienced the connections between concepts of citizenship and the influence of national government? It is my contention in the final instance that the Powwow, whilst not appealing to all audiences or constituents, does provide potential for the creation of an intermediary site that may connect people with each other, with the National Museum of the American Indian and other cultural centres, and with a range of other community and governmental services, initiatives, networks, and business opportunities that spin outwards from the Museum’s connections to federal government.